Application of In Situ Raman and Fourier Transform Infrared Spectroelectrochemical Methods on the Electrode‐Electrolyte Interface for Lithium−Oxygen Batteries. Issue 6 (18th February 2021) - Chen, Chunguang; Song, Mengyuan; Lu, Lingzhu; Yue, Lijuan; Huang, Tao; Yu, Aishui
Abstract: The development of rechargeable lithium−oxygen (Li−O2 ) batteries with high specific energy is essential to satisfy increasing energy consumption. It is critical to understand the dynamic process and detailed pathways during cell operation, which will allow us to control the reaction, suppress the formation of byproducts, and optimize battery performance. In situ vibrational spectroelectrochemical techniques, including in situ Raman spectroscopy and in situ Fourier Transform Infrared (FTIR) spectroscopy, are powerful analytical methods for the purposes of battery studies and are reviewed in this article. The two in situ techniques can acquire real‐time information of adsorbed species on the interface of the electrode, and reveal the reaction mechanism on the interface of the electrode/electrolyte in depth. In situ Raman technique mainly monitors intermediate species and products in Li−O2 batteries. The applications of surface‐enhanced Raman spectroscopy (SERS) for Li−O2 batteries are described in detail in the review. For the in situ FTIR technique, two commonly used in situ methods are introduced in Li−O2 batteries, namely, subtractive normalized Fourier transform infrared spectroscopy (SNIFTIRS) and attenuated total reflection surface enhanced infrared absorption spectroscopy (ATR‐SEIRAS). The reaction mechanism and failure mechanism of the cell are discussed by using the in situ FTIR technique. Abstract : Looking in situ : Understanding the reaction interfaces of lithium−oxygen batteries is essential to promote its development. In situ vibrational spectroelectrochemical techniques (Raman and Fourier Transform Infrared), which can monitor the subtle changes in the electrode‐electrolyte interfacial region, are crucial characterization methods. The information of intermediate and products can be obtained by the two methods, and then help us to gain an understanding of the mechanism deeply.